APICAL MICROLEAKAGE OF VARIOUS BIOMATERIALS IN SIMULATED IMMATURE APICES - Fatih Tulumbacı; Volkan Arıkan; Aylin Akbay Oba; İşıl Sönmez Şaroğlu (Selcuk Dental Journal)
Background:: In the treatment of open apex teeth, one-step apexiﬁcation has been reported as an alternative method to the use of long-term calcium hydroxide. Methods:The present study evaluated and compared apical microleakage when ProRoot MTA (Dentsply) (Group I), DiaRoot BioAggregate (Diadent) (Group II) and Biodentine (Septodont) (Group III) were used in the endodontic treatment of the teeth with simulated immature apices. In order to simulate immature teeth, 57 bovine maxillary incisor roots were prepared and randomly divided into three groups (n = 15 per group). The remaining teeth were included in negative (n=6) and positive (n=6) control groups. The materials were prepared according to the manufacturers instructions and a radiograph was taken for each sample to confirm proper obturation of the samples. Apical microleakage was assessed using the dye penetration technique. Linear dye penetration was measured at 30X magnification and the data were analyzed using ANOVA.Results:Group I showed the lowest apical leakage with a mean dye penetration of 4.64 mm, whereas the leakage was highest in Group II with a mean dye penetration of 5.45 mm. The difference between the leakage in Group I and II was statistically signiﬁcant (p<0.05), but the differences between other groups (Group I-III and Group II-III) were not (p > 0.05).Conclusions:The ﬁndings of the present study suggest that MTA has the best sealing ability when used for the obturation of immature apices. Keywords:BioAggregate, Biodentine, Endodontic treatment, Microleakage, MTA